Increase of the yields of eicosapentaenoic and docosahexaenoic acids by the microalga Pavlova lutheri following random mutagenesis - Meireles, Luís A. (2011)
The high commercial values of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids have driven a strain-improvement program, aimed at increasing the content of those fatty acids in the microalga Pavlova lutheri (SMBA 60) as parent strain. After a round of mutation using UV-light as mutagenic agent, an isolate strain (tentatively called II#2) was obtained, the EPA and DHA contents of which (in % dry biomass) were 32.8% and 32.9% higher than those of the control, native strain. The final EPA yields, when the cultures were maintained under appropriate conditions, were 17.4 and 23.1 mg · g−1 dry biomass, for the wild-type and the II#2 strain, respectively, whereas the final DHA yields were 8.0 and 10.6 mg · g−1 dry biomass, respectively. These results suggest that random mutagenesis can successfully be applied to increase the yield of n-3 fatty acids by microalgae.